Characterisation of biocatalysts immobilised in niobium—a new inorganic solid support. (14th February 2012) - Aguiar‐Oliveira, E.; Fernandes, P.; Cabral, J. M. S.; Maugeri, F.
Abstract A new support for enzyme immobilisation, an alloy of niobium ore and graphite, was tested with: invertase from baker's yeast and inulinase from Aspergillus niger. The efficiency of immobilisation was about 30% for invertase and 72% for inulinase. The maximum activities values were observed for both enzymes at: pH 4.5, 50°C and 500 g/L of sucrose. The hydrolysis of inulin (5% w/v) by the free inulinase and invertase presented specific productivity of reducing sugars lower after immobilisation, about 15 and 1.5 times, respectively; with the hydrolysis of sucrose (50% w/v) the reductions observed were of 14 and 3.5 times, respectively. © 2012 Canadian Society for Chemical Engineering